PENERAPAN LEAN WAREHOUSE PADA PROSES UNLOADING DAN LOADING DENGAN PENDEKATAN LEAN SUPPLY CHAIN - Agung Adi Sutarman (2020)
Increasing business development requires companies to improve their performance so that they can compete with other companies in the domestic and international markets. Performance improvements must be carried out continuously on all production lines in order to minimize waste (waste) that occurs by implementing lean warehouse. This research was conducted at PT. H with all activities in the warehouse. The purpose of this study is to determine what types of waste exist in warehouses that have the highest value. Big Image Mapping (BPM) is used to map the flow of information and the physical flow from the existing system to the hands of the final consumer. Questionnaires were distributed to discuss related parties in the warehouse about which waste was eliminated earlier, obtained the highest value waste. Value Stream Analysis Tools (VALSAT) methods to support waste. Identify the cause of the problem using Fault Tree Analysis (FTA). To utilize waste with one of the tools in the discussion of lean manufacturing, namely the waste assessment model (WAM) which is intended to manage the most dominant waste. From the results of the imposition of waste using the rubbish assessment model, the most dominant transportation of waste is transportation of 23.53%, operations of 17.12%, and delays of 15.86%. The results showed that the 3 biggest wastes that often occur are Waiting (Waiting) with a score of 4.8, Process that is not appropriate (Process that is not appropriate) with a total score of 2.4, and Defect (Product defects) with a score of 2.2. The value added from 25602 seconds to 14802 seconds and the time of no value added from 2388 seconds to 1381 seconds and necessary but not added value from 33340 seconds to 24686 seconds.